Boosting Islamic Bank Profitability: Governance, Disclosure, And Stakeholder Satisfaction - Putra, Donny Maha (LPPM ISNJ Bengkalis, 2024)
This study investigates how financial disclosure (SBFd), governance implementation (GGIsb), and social responsibility disclosure (SBSRd) affect profitability (SBP) and stakeholder satisfaction (SS), which are also mediating factors. This study uses a quantitative approach with secondary data in financial reports. The sample study involved 65 data of financial statements and reports annually collected during 2019-2022 from 13 Islamic Banks in Indonesia. The results show that SBFd and GGIsb positively impact SS and SBP. In contrast, SBSRd does not affect SBP and SS. Meanwhile, SS positively impacts SBP and has a good mediator effect on all correlations. This study confirms the stakeholder theory of the importance of transparency and good governance in improving the performance of finance and the mediating role of stakeholder satisfaction. Practical implications include recommendations to raise financial disclosure quality and strengthen governance mechanisms initiatives more effectively. The findings provide new insights for academics and practitioners in understanding the dynamics between operational factors and financially optimized banking sharia in the Indonesian context.